Diversity and Abundance of Echinoderms in Pancuran Beach, Lembeh Island - Christianti, Yudith; Boneka, Farnis; Kaligis, Erly; Wagey, Billy Th.; Sinjal, Chatrien A. L.; Lasabuda, Ridwan (Sam Ratulangi University, 2023)
Echinodermata are found quite commonly in the tidal areas of Lembeh Island but their diversity and abundance have not been well documented. The purpose of this study was to determine the types of Echinoderms and their abundance at Pancuran Beach, Lembeh Island, Bitung City. Samples were taken at two stations using the Lincoln-Smith Transect method 2 x 50 m which was stretched perpendicular to the beach with three replications. Samples were identified in situ and the number of individuals of each species was noted. The results showed that in Pancuran Beach there were 18 species of phylum Echinodermata; with details of 7 species from the Asteroidea class, 5 species of Echinoidea, 4 species of Ophiuroidea, 2 species of Holothuroidea. The results of the analysis using the diversity index show that the diversity of Echinodermata at both stations is in the medium category, characterized by the value of H' = 2.06 for station I and H'= 2.35 for station II. At station 1, the type of Ophiocoma erinaceus has the highest density of 15 ind/100m2 and a relative abundance of 23.68%. At station II Echinothrix diadema has the highest abundance of 12 ind/100m2 with a relative abundance of 17.14%. Common species found in both stations are Diadema setosum, Echinometra mathaei, Echinothrix diadema, Holothuria atra, Ophiocoma erinaceus, and Ophiocoma scolopendrina. Keywords: Lembeh Island, Diversity, Abundance, Echinoderms Abstrak Echinodermata ditemukan cukup umum di daerah pasang surut Pulau Lembeh namun keanekaragaman dan kelimpahannya belum sepenuhnya didokumentasikan dengan baik. Tujuan penelitian ini adalah untuk mengetahui jenis-jenis Echinodermata dan kelimpahannya di Pantai Pancuran, Pulau Lembeh Kota Bitung. Sampel diambil pada dua stasiun dengan menggunakan metode Lincoln-Smith Transect 2 x 50 m yang dibentangkan tegak lurus ke arah pantai dengan tiga replikasi. Sampel diidentifikasi secara insitu dan jumlah individu tiap spesies dicatat. Hasil menunjukkan bahwa di Pantai Pancuran terdapat 18 spesies filum Echinodermata; dengan rincian 7 spesies dari kelas Asteroidea, 5 spesies Echinoidea, 4 spesies Ophiuroidea, 2 spesies Holothuroidea. Hasil analisa menggunakan indeks keanekaragaman menunjukkan bahwa diversitas Echinodermata pada kedua stasiun dalam kategori sedang, ditandai dengan nilai H' = 2,06 untuk stasiun I dan H'= 2,35 untuk stasiun II. Pada stasiun 1, jenis Ophiocoma erinaceus paling tinggi densitasnya yakni 15 ind/100m2 dan kelimpahan relatif 23,68%, Pada stasiun II Echinothrix diadema memiliki kelimpahan tertinggi yakni 12 ind/100m2 dengan kelimpahan relatif 17,14%. Jenis yang umum terdapat pada kedua stasiun adalah Diadema setosum, Echinometra mathaei, Echinothrix diadema, Holothuria atra, Ophiocoma erinaceus, dan Ophiocoma scolopendrina. Kata kunci: Pulau Lembeh, Keanekaragaman, Kelimpahan, Echinodermata.